A simple broadcasting cryptosystem in computer networks using eXclusive-OR. (26th July 2005) - Lee, Cheng-Chi; Chang, Ting-Yi; Hwang, Min-Shiang
In 2002, Hwang et al. proposed a broadcasting cryptosystem in computer networks using the geometric properties of lines. Their scheme consumes less computing time and requires fewer public parameters than Wu and Wu's scheme. In this paper, the authors will propose a simple eXclusive-OR operation to live up to the requirements a good broadcasting cryptosystem should, and it even consumes less computing time and requires fewer public parameters than the Hwang et al. scheme.